Lingering effects associated with the consumer use of virtual reality - Porter III, John; Robb, Andrew (Frontiers in Virtual Reality, 2022)
3 Since the release of the Oculus Rift CV1 in 2016, millions of VR headsets have made their 4 way into consumers’ homes. Since then, users have created large quantities of data about their 5 experiences in VR through posts made to online discussion forums. We examine this data to 6 gain insights on what sorts of “lingering effects” users report having experienced after VR, and 7 on the progression of these effects over time. We found three major categories of lingering 8 effects (besides simulator sickness) during our qualitative analysis: perceptual effects, behavioral 9 effects, and changes in dreams. The perceptual and behavioral categories were further divided 10 into sub-themes: disruption of body ownership and proprioception, loss of a sense of depth in 11 the real world, visual aftereffects, the need to verify the reality of the real world through touch, 12 hesitation when moving in the real world, and attempts to apply VR interaction metaphors to real 13 life interactions. Users were nearly unanimous that these lingering effects only occurred after 14 spending at least one hour in VR, and that these effects completely disappeared several weeks 15 after they first appeared (assuming the user continued to spend time in VR). There was less 16 agreement about how long these effects lasted after exiting a specific VR session. The results of 17 our analysis suggest that users feel that there are no long-term side effects to the use of VR. We 18 pair this analysis with an analysis of interviews conducted with 20 novice users who were loaned 19 Oculus Quest HMDs to use for four weeks. Semi-structured interviews with participants further 20 substantiated the findings of our analysis of online discussions.